2009
DOI: 10.1177/00333549091244s112
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Control Technologies to Reduce Occupational Silica Exposures in Masonry Cutting and Tuckpointing

Abstract: SYNOPSISObjectives. A number of tasks in construction generate worker overexposures to respirable crystalline silica dust, which is a significant contributor to occupational mortality and morbidity. This study evaluated the performance of commercially available engineering controls used in dusty construction tasks commonly performed by bricklayers.Methods. Local exhaust ventilation (LEV) controls for a portable abrasive cutter and for tuckpointing grinders were examined at a bricklayers' training center, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 19 publications
(30 reference statements)
0
41
0
Order By: Relevance
“…Information from other sources, however, is needed to fill the existing gaps and to enable the goal-oriented approach typical of the job-specific WHS. In addition to information from literature published after the time frame of this review [e.g., Faber et al, 2009;Meeker et al, 2009;Hess et al, 2010], other methods such as a questionnaire survey, must be used in order to supplement and validate the evidence from the literature.…”
Section: Evidence Base Of Exposure Limitsmentioning
confidence: 99%
“…Information from other sources, however, is needed to fill the existing gaps and to enable the goal-oriented approach typical of the job-specific WHS. In addition to information from literature published after the time frame of this review [e.g., Faber et al, 2009;Meeker et al, 2009;Hess et al, 2010], other methods such as a questionnaire survey, must be used in order to supplement and validate the evidence from the literature.…”
Section: Evidence Base Of Exposure Limitsmentioning
confidence: 99%
“…In comparison, the mean PBZ respirable quartz concentration for the chisel tested here was 0.11 mg/m 3 . That represents a 77% reduction compared to one of the LEV-equipped grinders and a 67% reduction compared to the other LEV-equipped grinder in the Meeker et al [2009] study. However, even with that reduction, if the powered chisel with on-tool LEV was used for a full shift and dust levels remained constant and consistent with those observed in this study, the highest quartz concentration measured during use of the chisel, 0.16 mg/m 3 would be about 3 times the OSHA PEL and NIOSH REL.…”
Section: Discussionmentioning
confidence: 76%
“…For example, Meeker et al [2009] [Meeker et al 2009]. In comparison, the mean PBZ respirable quartz concentration for the chisel tested here was 0.11 mg/m 3 .…”
Section: Discussionmentioning
confidence: 82%
“…Researchers at NIOSH and CPWR began publishing research related to silica and engineering controls for silica beginning in 2003. [14][15][16][17][18][19][20] Research on a variety of LEV systems which involved measurement of silica exposure among tuckpointers using grinders, with and without controls, continued into the current decade. These studies have led to published recommendations for improving LEV design, focusing on grinder shrouds, minimum air flows needed for effective dust capture and ease of use.…”
Section: The Role Of Researchmentioning
confidence: 99%
“…By the first decade of the new millennium, ample research demonstrated that silica exposures were pervasive in construction and that effective engineering controls were available. [14][15][16][17][18][19][20] In 1992, NIOSH Director Dr. J. Donald Millar developed a national program to eradicate silicosis, which he described as "an occupational obscenity." Joint prevention efforts on the part of OSHA, NIOSH, and the Mine Safety and Health Administration kicked off a national public education campaign in 1996 with the theme -Silica: It's not just dust and NIOSH Alerts were published and disseminated widely.…”
mentioning
confidence: 99%